Systematic investigations on the effect of prolong UV illumination on optoelectronic properties of ZnO honeycomb nanostructures. (1st April 2019) - Agrawal, Jitesh; Dixit, Tejendra; Palani, I.A.; Singh, Vipul
Abstract: Herein, the effect of prolong UV illumination over ZnO optoelectronic characteristics has been investigated. The photoluminescence analysis has shown significant enhancement in deep level emission (DLE) after sample being exposed to UV radiations. The formation of photo-induced oxygen vacancies (VO ) over the ZnO surface was found to be responsible for such noteworthy enhancement in DLE. The observed phenomenon was further utilized for controlled incorporation of VO in ZnO via UV illumination, towards obtaining optimal device performance. The UV treated photo-detector has shown significantly high photo-responsivity and photo-sensitivity in the deep UV region. Graphical abstract: Unlabelled Image